Two cases of neonatal adrenal hemorrhage presenting with persistent jaundice - E. Ruffini; L. De Petris; P. Paoletti; G. Mambelli; A. Carlucci (PAGEPress Publications, 2013)
The adrenal hemorrhage is a relatively rare event in newborns but must be considered in the presence of a persistent unexplained jaundice, especially in presence of predisposing factors. Serial ultrasonography is the modality of choice for initial diagnosis and follow-up of neonatal adrenal hemorrhage. We report two cases of neonatal adrenal hemorrhage presenting with persistent jaundice. The causes of the neonatal adrenal hemorrhages were a difficult vaginal delivery in macrosomic infant and a neonatal infection.